2018
DOI: 10.3389/fpls.2018.01850
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidal Activity and Molecular Docking Study of Novel ACCase Inhibitors

Abstract: Acetyl-CoA carboxylase (ACCase) is an important target enzyme for the development of new bleaching herbicides. On the basis of structure-activity relationships and active subunit combinations, a series of novel 2-phenyl-3-cyclohexanedione enol ester derivatives was designed and synthesized by coupling and acylation reactions. The preliminary biological tests indicated good post-emergent herbicidal activity at a dosage of 150–300 g ai/ha, superior to that of clethodim against barnyard grass. Compound 3d was saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Molecular modelling was performed to study the complexation between host molecules and guest molecules. 28,29 The molecular model in Fig. 9 was the lowest energy model obtained by molecular modelling.…”
Section: Results Of Molecular Modellingmentioning
confidence: 99%
“…Molecular modelling was performed to study the complexation between host molecules and guest molecules. 28,29 The molecular model in Fig. 9 was the lowest energy model obtained by molecular modelling.…”
Section: Results Of Molecular Modellingmentioning
confidence: 99%
“…Yan et al reported a novel aryloxyphenoxypropionate herbicide based on benzofuran and investigated its possible herbicidal mechanism by molecular docking [22]. The molecular docking experiment performed by Ye et al [11,23] suggested that the reason that the safener had a protective effect might be due to competition between the safener and the herbicide in the target enzyme active pocket.…”
Section: Introductionmentioning
confidence: 99%
“…It is an important enzyme in the tyrosine metabolic pathway, belonging to the large family of 2-his-1-carboxylate facial triad oxidative enzymes. As an important enzyme correlated to the pigment synthesis and tyrosine catabolism in most organisms, HPPD is important in agricultural areas [14]. A large number of HPPD inhibitors have been discovered, researched and applied to control weed in the field of agrochemicals in recent several decades [15].…”
Section: Discussionmentioning
confidence: 99%